Green energy solutions: Humidity-driven power generation using NiO/G composites on recycled paper - Nurul Syafiqah Mohamed Mustakim; Dayana Kamaruzaman; A. Shamsul Rahimi Bin A. Subki; Mohd Hanapiah Abdullah; Mohd Firdaus Malek; Norfarariyanti Parimon; Mohd Khairul Ahmad; Suriani Abu Bakar; Nagamalai Vasimalai; Mohamad Hafiz Mamat (American Institute of Physics Inc., 2025)
Humidity energy harvesting is a significant advance in the field of renewable energy that presents a promising solution to satisfy energy demands while also addressing environmental concerns. Paper waste is a major environmental problem that contributes to air pollution, landfills, deforestation, and energy consumption. This research aims to convert waste into energy by utilizing recycled paper as a substrate for a humidity-to-energy device. We successfully prepared our own recycled paper via a straightforward procedure, which was then employed in the device. In this study, nickel oxide/graphene (NiO/G) composite was applied as the hygroscopic material using the sonicated solution immersion method. At 75% relative humidity, the humidity-to-energy device demonstrated an output voltage of0.683 mV, a current density of 0.055 nA/cm2, and a power output of 0.047 pW. These results highlight the potential to turn wastepaper into useful materials for energy harvesting applications, boosting the development of renewable energy technologies and sustainable practices.